Reducing GBV risks through better shelter programme design - Rule, A; Izquierdo, J; Piccioli, A (Refugee Studies Centre, University of Oxford, 2017)
Good shelter programming must include mitigation measures throughout the project cycle in order to reduce GBV risks.